Understanding the Integrity of Coating for Taste-Masked Granules - Before and After Tablet Compression - Manish Ghimire (University of Huddersfield Press, 2018)
Raman microscopy was used to visualize the integrity of a barrier membrane coating at the various stage of chewable tablets development. The effect of substrate morphology and particle characteristics was found to be important in maintaining the integrity of the coating throughout the process of chewable tablets manufacture. Furthermore, the observations from the Raman image analysis provide an understanding of the factors affecting drug release.